2010
DOI: 10.1111/j.1365-2958.2010.07303.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen levels rapidly modulate Pseudomonas aeruginosa social behaviours via substrate limitation of PqsH

Abstract: SummaryMany bacteria use extracellular signals to coordinate group behaviours, a process referred to as quorum sensing (QS). The bacterium Pseudomonas aeruginosa utilizes a complex QS system to control expression of over 300 genes, including many involved in host colonization and disease. The Pseudomonas quinolone signal (PQS) is a component of P. aeruginosa QS, and although it contributes to virulence in some models of infection, the PQS biosynthetic pathway is not fully elucidated. Here, we show that PqsH ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
157
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(165 citation statements)
references
References 63 publications
6
157
0
2
Order By: Relevance
“…In contrast, our data suggested that PAO1 produced significantly suppressed levels of PAI-1 and nondetectable PAI-2 during anaerobic growth, respectively. Together with previous reports revealing that the production of PQS is also highly inhibited during anaerobic growth (43,51), these findings suggest that (i) the three major autoinducers mediating P. aeruginosa QS are either not produced or produced at significantly lower levels during anaerobic growth and (ii) QS may therefore not be functional in PAO1 growing under anaerobic conditions. It is of particular interest that the levels of PAI-1 and PAI-2 detected in sputum samples isolated from CF patients colonized with up to 10 8 CFU/ml of P. aeruginosa were significantly lower than those produced in laboratory aerobic cultures (46).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In contrast, our data suggested that PAO1 produced significantly suppressed levels of PAI-1 and nondetectable PAI-2 during anaerobic growth, respectively. Together with previous reports revealing that the production of PQS is also highly inhibited during anaerobic growth (43,51), these findings suggest that (i) the three major autoinducers mediating P. aeruginosa QS are either not produced or produced at significantly lower levels during anaerobic growth and (ii) QS may therefore not be functional in PAO1 growing under anaerobic conditions. It is of particular interest that the levels of PAI-1 and PAI-2 detected in sputum samples isolated from CF patients colonized with up to 10 8 CFU/ml of P. aeruginosa were significantly lower than those produced in laboratory aerobic cultures (46).…”
Section: Discussionsupporting
confidence: 78%
“…Schertzer and colleagues recently elucidated the molecular basis behind the abrogated synthesis of PQS during growth without oxygen (43). Because oxygen and NADH are required as cofactors for the enzymatic synthesis of PQS from its precursor, 2-heptyl-4-quinolone (HHQ), a lack of oxygen prevents the enzymatic conversion of HHQ to PQS from taking place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3D). We reasoned that the lack of iron-regulated growth suppression of S. mutans could be due to reduced PQS production during static growth in the transwell plates, as PQS production is known to be dependent upon oxygen (50). However, iron-regulated AQ production not only was retained under these conditions but was significantly enhanced during static versus shaking growth (see Fig.…”
Section: Iron Regulates Pqsa-mediated Growth Suppression Of S Aureusmentioning
confidence: 99%
“…Subsequent investigations of these genes have yielded a wealth of knowledge about the precursors and biosynthesis of PQS in P. aeruginosa (20)(21)(22)(23). One of the mutants was found to have a disruption in gene PA5506 (hereafter referred to as qapR for quinolone alteration pathway regulator), which encodes an RpiR family transcriptional regulator homolog.…”
mentioning
confidence: 99%